AB1177 HOW TO DEFINE RHUPUS SYNDROME: SYSTEMATIC REVIEW OF THE CURRENT LITERATURE. (June 2019) - Rubini, Elena; Foddai, Silvia Grazietta; Radin, Massimo; Cecchi, Irene; Rossi, Daniela; Sciascia, Savino; Roccatello, Dario
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by the presence of multi-systemic manifestations in patients with immunologic anomalies. While joint involvement is present in up to 90% of patients with SLE [1], only a small subset of patients develops erosive arthritis. The term rhupus refers to the coexistence of erosive symmetrical polyarthritis, typical manifestation of rheumatoid arthritis (RA), and clinical signs of SLE in the presence of anti double-stranded DNA (anti-dsDNA) and/or anti-Smith antibodies (anti-Sm) [2]. However, to date, no consensus exists on how to define the rhupus syndrome. Objectives: In this study we aim to investigate the definition of rhupus by systematically reviewing the current literature. Methods: A detailed literature research has been developed a priori to identify articles that reported findings from rhupus patients. The search strategy was applied to Ovid MEDLINE In-Process and Other Non-Indexed Citation 2000 to present. Studies that included rhupus patients were systematically analyzed by two independent reviewers (ER and SGF). Disagreements were resolved by consensus; if consensus could not be achieved, a third party (MR) would provide an assessment of eligibility. Results: We analyzed clinical and serological data of 176 patients with diagnosis of rhupus derived from a total of 16 studies. All works considered the presence of autoantibodies specific for SLE by including anti-nuclear antibodies (ANA), anti-dsDNA, and anti-Sm antibodies. Only 67% of patients had ANA positivity (119/176), 64% showed anti-dsDNA in serum (113/176) and 17% were positive for anti-Sm antibodies. No heterogeneous data were available on pattern or title of these autoantibodies. Only two studies did not assay ANA or anti-dsDNA. Twelve out of 16 studies tested the occurrence of anti-citrullinated peptide antibodies (ACPAs) that have been reported in 73 patients (41%), rheumatoid factor (RF) was detected in 149 patients (84%) resulting from 13 out of 16 studies. Among clinical criteria of rhupus, an erosive arthritis has been observed in 155 patients (88%), only one study did not take into account the joint erosion. Hematological and cutaneous disorders (64% and 86%, respectively) were the most frequent extra-articular manifestations of SLE. Few patients experienced main systemic signs such as renal (67 patients, 38%) and neurological (9 patients, 5%) disorders, vasculitis (6 patients, 3%), and sierositis (43 patients, 24%). The studies included in the present analysis are displayed in Table 1 . Conclusion: We observed a strong heterogeneity in the elements taken into account to establish the presence of rhupus, reflecting the lack of consensus and validated criteria to define the disease. Rhupus can represent an aggressive and disabling condition, and a harmonization in the classification criteria might represent the first step to improve the management of these patients. References: [1] Ceccarelli F, et al. The role of disease activity score 28 in the evaluation of articular involvement in systemic lupus erythematosus. ScientificWorldJournal. 2014; 2014: 236842. [2] Lozada-Navarro, et al. An imbalance in the T-helper phenotypes displayed by senescent CD4 CD28null T cells is associated with erosive arthritis (rhupus syndrome) in systemic lupus erythematosus. Lupus. 2018 Nov;27(13):2155-2160. Disclosure of Interests: None declared